Long-term outcomes of a randomized, open-label, phase II study comparing cabazitaxel versus paclitaxel as neoadjuvant treatment in patients with triple-negative or luminal B/HER2-negative breast cancer (GENEVIEVE) - Meyer-Wilmes, P.; Huober, J.; Untch, M.; Blohmer, J. U.; Janni, W.; Denkert, C.; Klare, P.; Link, T.; Rhiem, K.; Bayer, C.; Reinisch, M.; Bjelic-Radisic, V.; et al. (ESMO Open, 2024)
Background: The GENEVIEVE study, comparing neoadjuvant cabazitaxel versus paclitaxel in triple-negative breast cancer (TNBC) and luminal B/human epidermal growth factor receptor 2 (HER2)-negative breast cancer (BC), previously reported significant differences in pathological complete response (pCR) rates. Effects on long-term outcome are unknown. Patients and methods: GENEVIEVE randomized patients with cT2-3, any cN or cT1, cN+/pNSLN+, centrally confirmed TNBC or luminal B/HER2-negative BC (latter defined as estrogen/progesterone receptor-positive and >14% Ki-67-stained cells) to receive either cabazitaxel 25 mg/m2 q3w for four cycles or paclitaxel 80 mg/m2 weekly for 12 weeks. Anthracycline-containing chemotherapy was allowed in case of histologically proven invasive residuals as neoadjuvant treatment or after surgery as adjuvant treatment. Here we report the secondary endpoints invasive disease-free survival (iDFS), distant disease-free survival (DDFS), and overall survival (OS). Results: Of the 333 patients randomized, 74.7% and 83.2% completed treatment in the cabazitaxel and paclitaxel arms, respectively. After a median follow-up of 89.3 months (interquartile range 68.8-97.3 months), 80 iDFS events (43 after cabazitaxel and 37 after paclitaxel) and 47 deaths (23 after cabazitaxel and 24 after paclitaxel) were reported. IDFS rates were not significantly different between the cabazitaxel and paclitaxel arms after a 3-year (83.6% versus 85.0%) and 5-year follow-up (76.2% versus 78.3%) [hazard ratio (HR) = 1.27, 95% confidence interval 0.82-1.96, P = 0.294], respectively. DDFS rates at 3 years (88.6% versus 87.8%) and 5 years (82.1% versus 82.8%) for cabazitaxel and paclitaxel were comparable (HR = 1.15, P = 0.573). Similarly, OS rates at 3 years (91.6% versus 91.8%) and 5 years (89.2% versus 86.8%) showed no significant differences (HR = 1.05, P = 0.872). Subgroup analysis for TNBC and luminal B/HER2-negative BCs indicated no significant variations in 3- or 5-year iDFS, DDFS, or OS. Conclusions: The significant differences in pCR rates observed in both treatment arms did not significantly impact long-term outcomes for patients treated with cabazitaxel versus paclitaxel in the GENEVIEVE trial.
CRIS-Team Scopus Importer:2024-05-03
Keywords: breast cancer; cabazitaxel; HER2-negative; paclitaxel; survival